Treatment method of phosphogypsum

By mixing phosphogypsum with carbon materials, siliceous materials and aluminum materials for decomposition and calcination, the problem of high cost of phosphogypsum decomposition process is solved, efficient and low-cost phosphogypsum treatment is achieved, and the economy and adaptability of phosphochemical industry is improved.

CN119612986APending Publication Date: 2025-03-14WENGFU (GRP) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077081.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing phosphogypsum decomposition process is costly, which has hindered technological development and promotion, making it difficult to achieve high-quality development of phosphochemical industry.

Method used

By mixing phosphogypsum with carbon material, siliceous material and aluminum material and decomposing and calcining, cement products are obtained, reducing the treatment cost of phosphogypsum.

Benefits of technology

The decomposition rate of phosphogypsum is improved, and the production cost is reduced, thereby improving the economic and adaptability of the decomposition process of phosphogypsum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005247414860000081
    Figure BDA0005247414860000081
Patent Text Reader

Abstract

The invention relates to the technical field of phosphorus chemical industry, in particular to an ardealite treatment method which comprises the following steps: S1) drying ardealite to obtain semi-hydrated ardealite; s2) mixing the semi-hydrated phosphogypsum, the carbon material, the siliceous material and the aluminum material, and homogenizing; the carbon material is coke and anthracite, and the molar content of the anthracite in the carbon material is 0-50% and is not 0; or the carbon material is coke and petroleum coke, and in the carbon material, the molar content of the petroleum coke is 0-100% and is not 0; s3) preheating the obtained homogenized material to 600-700 DEG C, and decomposing the homogenized material at 900-1200 DEG C to obtain a decomposed mixed material; s4) calcining the decomposed mixture at the temperature of 1300-1500 DEG C to obtain cement clinker; s5) mixing the cement clinker and the mixed material, and grinding to obtain a cement product; the mixed material comprises phosphogypsum and coal ash. According to the treatment method provided by the invention, the decomposition rate of the ardealite is relatively high, and the cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phosphorus chemical industry, and in particular to a method for treating phosphogypsum. Background Art

[0002] At present, the decomposition processes of phosphogypsum include sulfur reduction, carbon monoxide reduction, hydrogen reduction, hydrogen sulfide reduction and carbon reduction, and the carbon reduction process has the best industrial application effect. The existing carbon reduction process can only use relatively expensive coke and bituminous coal, and the production cost is high (converted to a ton, the cost of phosphogypsum treatment is nearly 400 yuan), which is unaffordable for enterprises, resulting in serious obstruction of the development and promotion of phosphogypsum decomposition technology, and ultimately restricting the high-quality development of phosphorus chemical industry. Summary of the invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a method for treating phosphogypsum, which has a higher decomposition rate of phosphogypsum and lower cost.

[0004] The present invention provides a method for treating phosphogypsum, comprising the following steps:

[0005] S1) drying the phosphogypsum to obtain hemihydrate phosphogypsum;

[0006] S2) mixing the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material, and homogenizing;

[0007] The carbon material is coke and anthracite, and the molar content of anthracite in the carbon material is 0 to 50%, and is not 0; or the carbon material is coke and petroleum coke, and the molar content of petroleum coke in the carbon material is 0 to 100%, and is not 0;

[0008] S3) preheating the homogenized material obtained in step S2) to 600-700° C., and then decomposing it at 900-1200° C. to obtain a decomposed mixed material containing SO2 flue gas and CaO;

[0009] S4) calcining the CaO-containing decomposition mixture at 1300-1500° C. to obtain cement clinker;

[0010] S5) mixing the cement clinker and mixed materials, and grinding them to obtain a cement product; the mixed materials include phosphogypsum and fly ash.

[0011] Preferably, in step S2), in the siliceous material, the mass content of SiO2 is 75% to 90%, and the mass content of P2O5 is less than 0.15%;

[0012] The particle size of the siliceous material does not exceed 25 mm.

[0013] Preferably, in step S2), in the aluminum material, the mass content of Al2O3 is ≥45%, and the mass content of P2O5 is <0.15%;

[0014] The particle size of the aluminum material does not exceed 25 mm.

[0015] Preferably, in step S2), the particle size of the carbon material does not exceed 25 mm.

[0016] Preferably, in step S2), the mass ratio of the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material is 88-95: 3-5: 1.5-4.8: 0.5-2.5.

[0017] Preferably, in step S3), the mass content of the decomposed atmosphere O2 is controlled to be less than 3% and the time is 60 to 90 minutes.

[0018] Preferably, in step S4), the calcination time is 13 to 17 minutes.

[0019] Preferably, in step S5), the mass ratio of the phosphogypsum to the fly ash is 3-5:10-15.

[0020] Preferably, in step S5), the mass ratio of the cement clinker to the mixed material is 80-90:10:20.

[0021] Preferably, in step S5), the specific surface area of ​​the ground cement product is controlled to be 300-350 m 2 / kg.

[0022] The invention provides a method for treating phosphogypsum, comprising the following steps: S1) drying the phosphogypsum to obtain hemihydrate phosphogypsum, and providing sulfur elements for downstream processes; S2) mixing the hemihydrate phosphogypsum, a carbon material, a siliceous material and an aluminum material, and homogenizing the mixture; the carbon material is coke and anthracite, and the molar content of the anthracite in the carbon material is 0-50%, and is not 0; or the carbon material is coke and petroleum coke, and the molar content of the petroleum coke in the carbon material is 0-100%, and is not 0; S3) preheating the homogenized material obtained in step S2) to 600-700° C., and decomposing it at 900-1200° C. to obtain a decomposed mixed material containing SO2 flue gas and CaO; S4) calcining the decomposed mixed material at 1300-1500° C. to obtain cement clinker; S5) mixing the cement clinker and a mixed material, and grinding them to obtain a cement product; the mixed material comprises phosphogypsum and fly ash. The treatment method provided by the present invention enables the decomposition rate of phosphogypsum to be higher and the cost to be lower, thereby fundamentally improving the economy and adaptability of the phosphogypsum decomposition process. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention provides a method for treating phosphogypsum, comprising the following steps:

[0025] S1) drying the phosphogypsum to obtain hemihydrate phosphogypsum;

[0026] S2) mixing the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material, and homogenizing;

[0027] The carbon material is coke and anthracite, and the molar content of anthracite in the carbon material is 0 to 50%, and is not 0; or the carbon material is coke and petroleum coke, and the molar content of petroleum coke in the carbon material is 0 to 100%, and is not 0;

[0028] S3) preheating the homogenized material obtained in step S2) to 600-700° C., and then decomposing it at 900-1200° C. to obtain a decomposed mixed material containing SO2 flue gas and CaO;

[0029] S4) calcining the CaO-containing decomposition mixture at 1300-1500° C. to obtain cement clinker;

[0030] S5) mixing the cement clinker and mixed materials, and grinding them to obtain a cement product; the mixed materials include phosphogypsum and fly ash.

[0031] Regarding step S1):

[0032] Phosphogypsum is dried to obtain hemihydrate phosphogypsum, which provides sulfur for downstream processes.

[0033] In certain embodiments of the present invention, the phosphogypsum has a crystal water content of 4% to 12% (mass content), such as 9%.

[0034] In certain embodiments of the present invention, the drying temperature is 800-900° C., such as 900° C. The crystal water content of the hemihydrate phosphogypsum is 4%-12% (mass content), such as 8%.

[0035] Regarding step S2):

[0036] The hemihydrate phosphogypsum, carbon material, siliceous material and aluminum material are mixed and homogenized;

[0037] The carbon material is coke and anthracite; in the carbon material, the molar content of anthracite is 0-50% and is not 0; or the carbon material is coke and petroleum coke; in the carbon material, the molar content of petroleum coke is 0-100% and is not 0.

[0038] In certain embodiments of the present invention, the particle size of the carbon material does not exceed 25 mm; specifically, does not exceed 80 μm.

[0039] In certain embodiments of the present invention, the mass content of SiO2 in the siliceous material is 75% to 90%, such as 85%; the mass content of P2O5 is less than 0.15%, such as 0.1%. The siliceous material may be silica. The particle size of the siliceous material does not exceed 25 mm; specifically, does not exceed 80 μm.

[0040] In certain embodiments of the present invention, in the aluminum material, the mass content of Al2O3 is ≥45%, such as 40%; the mass content of P2O5 is <0.15%, such as 0.1%. The aluminum material may be bauxite. The particle size of the aluminum material does not exceed 25 mm; specifically, does not exceed 80 μm.

[0041] In certain embodiments of the present invention, the mass ratio of the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material is 88-95:3-5:1.5-4.8:0.5-2.5; for example, 90:4:3:1.5.

[0042] In certain embodiments of the present invention, in the mixed material of the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material, the C / S molar ratio is 0.6 to 0.75:1, such as 0.7:1.

[0043] The mixing can be performed in a mixer.

[0044] Regarding step S3):

[0045] The homogenized material obtained in step S2) is preheated to 600-700°C and then decomposed at 900-1200°C to obtain a decomposed mixed material containing SO2 flue gas and CaO.

[0046] In certain embodiments of the present invention, the preheating is performed in a cyclone preheater at the end of the clinker burning kiln. The preheating time is 8 to 15 seconds, such as 10 seconds.

[0047] The preheating heat is provided by the bituminous coal powder after being burned in the coal powder burner. The gas after the combustion of the coal powder burner enters the sulfuric acid device.

[0048] In certain embodiments of the present invention, the mass content of O2 in the decomposition atmosphere is controlled to be less than 3%, and the time is 60 to 90 minutes. The decomposition is carried out in a rotary kiln.

[0049] In the SO2-containing flue gas, the mass content of SO2 is 10% to 12%, for example, 11%.

[0050] In certain embodiments of the present invention, after the decomposition, the process further includes: passing the SO2-containing flue gas (i.e., kiln gas containing SO2) into countercurrent contact with the raw material through a cyclone preheater, performing heat exchange, and then passing through an electrostatic precipitator to remove dust before entering the sulfuric acid device.

[0051] The raw material includes SiO2, Al2O3, Fe2O3, CaO, MgO and SO3; in the raw material, the ignition loss is 13.5% to 14.5%, such as 14%; the mass content of SiO2 is 10% to 11.5%, such as 11%; the mass content of Al2O3 is 1.5% to 2.5%, such as 2%; the mass content of Fe2O3 is 0.7% to 1%, such as 0.9%; the mass content of CaO is greater than 30%, such as 31%; the mass content of MgO is 0 to 0.3%, and is not 0, such as 0.2%; the mass content of SO3 is greater than 40%, such as 40.9%. The present invention has no special restrictions on the source of the raw material.

[0052] Regarding step S4):

[0053] The CaO-containing decomposition mixture is calcined at 1300-1500° C. to obtain cement clinker.

[0054] In certain embodiments of the present invention, the calcination temperature is 1400° C., the calcination time is 13 to 17 minutes, such as 15 minutes, and the calcination is carried out in a rotary kiln.

[0055] In the present invention, in the rotary kiln, the main reactions of gypsum decomposition and clinker burning occur. The CaO generated by the decomposition of gypsum reacts with SiO2, Al2O3, Fe2O3 (one of the components of phosphogypsum) and the like in the ingredients to form the four main mineral components of cement clinker, namely tricalcium silicate (C3S), dicalcium silicate (C2S), tricalcium aluminate (C3A), and tetracalcium aluminoferrite (C4AF). The chemical decomposition of gypsum is divided into two steps, as shown in formula (1) and formula (2);

[0056] CaSO4+2C→CaS+2CO2↑ Formula (1);

[0057] 3CaSO4+CaS→4CaO+4SO2↑ Formula (2);

[0058] The overall reaction is shown in formula (3): 2CaSO4+C→2CaO+2SO2↑+CO2↑Formula (3).

[0059] Regarding step S5):

[0060] The cement clinker and mixed materials are mixed and then ground to obtain a cement product; the mixed materials include phosphogypsum and fly ash.

[0061] In certain embodiments of the present invention, the mass ratio of phosphogypsum to fly ash is 3-5:10-15, such as 3:12.

[0062] In certain embodiments of the present invention, the mass ratio of the cement clinker to the mixed material is 80-90:10:20, such as 85:15.

[0063] In certain embodiments of the present invention, the grinding is carried out in a cement mill. The specific surface area of ​​the cement product after grinding is controlled to be 300-350m 2 / kg.

[0064] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0065] In order to further illustrate the present invention, a method for treating phosphogypsum provided by the present invention is described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0066] The parameters of the phosphogypsum used in the embodiment are as follows: the crystal water content of the phosphogypsum is 9% (mass content).

[0067] Example 1

[0068] 1) drying 220 t of phosphogypsum at 900° C. to obtain hemihydrate phosphogypsum; the hemihydrate phosphogypsum has a crystal water content of 8%;

[0069] 2) mixing the hemihydrate phosphogypsum, carbon material (coke and anthracite, with a molar ratio of 4:1 and a particle size not exceeding 80 μm), silica (with a mass content of SiO2 of 85%, a mass content of P2O5 of 0.001%, and a particle size not exceeding 80 μm), and bauxite (with a mass content of Al2O3 of 40%, a mass content of P2O5 of 0.001%, and a particle size not exceeding 80 μm) in a mixer, and then homogenizing in a homogenizing tank to obtain a homogenized material;

[0070] The mass ratio of the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material is 90:4:3:1.5;

[0071] In the material after the hemihydrate phosphogypsum, carbon material, siliceous material and aluminum material are mixed, the C / S molar ratio is 0.7:1;

[0072] 3) preheating the homogenized material in a cyclone preheater at the end of a clinker kiln (preheating rate is 10s) to 650°C, and then decomposing it in a rotary kiln (the mass content of O2 in the atmosphere is controlled at 2%, the temperature is 1150°C, and the time is 80min) to obtain a SO2-containing flue gas (the mass content of SO2 is 11%) and a decomposed mixed material containing CaO;

[0073] The preheating heat is provided by the bituminous coal powder after being burned in the coal powder burner; the gas after the combustion of the coal powder burner enters the sulfuric acid device;

[0074] The SO2-containing flue gas is brought into countercurrent contact with the raw meal through a cyclone preheater for heat exchange, and then is dedusted by an electrostatic precipitator before entering the sulfuric acid device;

[0075] The raw meal includes SiO2, Al2O3, Fe2O3, CaO, MgO and SO3; in the raw meal, the loss on ignition is 14%; the mass content of SiO2 is 11%; the mass content of Al2O3 is 2%; the mass content of Fe2O3 is 0.9%; the mass content of CaO is 31%; the mass content of MgO is 0.2% and the mass content of SO3 is 40.9%.

[0076] 4) calcining the decomposed mixture at 1400° C. for 15 min to obtain cement clinker;

[0077] 5) After the cement clinker and the mixed materials are mixed, they are ground in a cement mill, and the specific surface area of ​​the ground cement product is controlled to be 300-350m 2 / kg, and obtain cement products;

[0078] The mixed material is phosphogypsum and fly ash, with a mass ratio of 3:12; the mass ratio of cement clinker and the mixed material is 85:15.

[0079] Example 2

[0080] The difference from Example 1 is:

[0081] In step 2), the molar ratio of coke to anthracite is 1:1;

[0082] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0083] Comparative Example 1

[0084] The difference from Example 1 is:

[0085] In step 2), the carbon materials are all coke;

[0086] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0087] Comparative Example 2

[0088] The difference from Example 1 is:

[0089] In step 2), the molar ratio of coke to anthracite is 1:4;

[0090] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0091] Comparative Example 3

[0092] The difference from Example 1 is:

[0093] In step 2), the carbon materials are all anthracite;

[0094] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0095] Example 3

[0096] The difference from Example 1 is:

[0097] In step 2), the carbon material is coke and petroleum coke in a molar ratio of 4:1;

[0098] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0099] Example 4

[0100] The difference from Example 1 is:

[0101] In step 2), the carbon material is coke and petroleum coke in a molar ratio of 1:1;

[0102] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0103] Example 5

[0104] The difference from Example 1 is:

[0105] In step 2), the carbon material is coke and petroleum coke in a molar ratio of 1:4;

[0106] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0107] Example 6

[0108] The difference from Example 1 is:

[0109] In step 2), the carbon material is petroleum coke;

[0110] The remaining steps and parameters are the same as those in Example 1 to obtain a cement product.

[0111] The decomposition rates and costs of Examples 1 to 6 and Comparative Examples 1 to 3 were studied, and the results are shown in Table 1. The decomposition rate refers to the decomposition rate of step 3); the cost refers to the cost reduction value compared to Comparative Example 1 using coke.

[0112] Table 1 Decomposition rate and cost of Examples 1 to 6 and Comparative Examples 1 to 3

[0113]

[0114] As can be seen from Table 1, the experimental decomposition rate of coke is 95.2%; when all anthracite is used, the experimental decomposition rate of phosphogypsum is 91.5%; when the anthracite blending ratio is reduced to 80%, the experimental decomposition rate is 92.3%, and the decomposition rate is slightly increased; when the anthracite blending ratio is reduced to 50%, the experimental decomposition rate is 93.8%, and the decomposition rate is slightly increased; when the anthracite blending ratio is reduced to 20%, the experimental decomposition rate is consistent with coke, and the effect is best. Combined with the actual production test situation, when the anthracite blending ratio is 50%, various production indicators are relatively stable and can meet the actual production requirements. Therefore, in the carbon material, the molar content of anthracite is 0-50%, and is not 0; according to the market unit price of anthracite and coke, the difference is calculated as 1,000 yuan / ton. Compared with the case of using coke, the cost per ton of the product of the present invention can be reduced by 25 to 40 yuan.

[0115] The experimental decomposition rate of coke is 95.2%; when all petroleum coke is used, the experimental decomposition rate of phosphogypsum is 95%, which is equivalent to the decomposition rate of coke; when the petroleum coke blending ratio is reduced to 80%, the experimental decomposition rate is 93.8%, and the decomposition rate decreases slightly; when the petroleum coke blending ratio is reduced to 50%, the experimental decomposition rate is 95.2%, which is consistent with coke and has the best effect; when the petroleum coke blending ratio is reduced to 20%, the experimental decomposition rate is 94.2%, and the decomposition rate has recovered. Combined with the actual production test situation, when the petroleum coke blending ratio is 0% to 100% and not 0, various production indicators are relatively stable and can meet the actual production requirements. Therefore, in the carbon material, the molar content of petroleum coke is 0 to 100%, and not 0. According to the market unit price of petroleum coke and coke, the difference is calculated as 1,000 yuan / ton. Compared with the case of using coke, the cost per ton of the product of the present invention can be reduced by 25 to 50 yuan.

[0116] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for treating phosphogypsum, comprising the following steps: S1) drying the phosphogypsum to obtain hemihydrate phosphogypsum; S2) mixing the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material, and homogenizing; The carbon material is coke and anthracite, and the molar content of anthracite in the carbon material is 0 to 50%, and is not 0; or the carbon material is coke and petroleum coke, and the molar content of petroleum coke in the carbon material is 0 to 100%, and is not 0; S3) preheating the homogenized material obtained in step S2) to 600-700° C., and then decomposing it at 900-1200° C. to obtain a decomposed mixed material containing SO2 flue gas and CaO; S4) calcining the CaO-containing decomposition mixture at 1300-1500° C. to obtain cement clinker; S5) mixing the cement clinker and mixed materials, and grinding them to obtain a cement product; the mixed materials include phosphogypsum and fly ash.

2. The processing method according to claim 1, characterized in that: In step S2), in the siliceous material, the mass content of SiO2 is 75% to 90%, and the mass content of P2O5 is less than 0.15%; The particle size of the siliceous material does not exceed 25 mm.

3. The processing method according to claim 1, characterized in that: In step S2), in the aluminum material, the mass content of Al2O3 is ≥45%, and the mass content of P2O5 is <0.15%; The particle size of the aluminum material does not exceed 25 mm.

4. The processing method according to claim 1, characterized in that: In step S2), the particle size of the carbon material does not exceed 25 mm.

5. The processing method according to claim 1, characterized in that: In step S2), the mass ratio of the hemihydrate phosphogypsum, the carbon material, the siliceous material and the aluminum material is 88-95: 3-5: 1.5-4.8: 0.5-2.

5.

6. The processing method according to claim 1, characterized in that: In step S3), the mass content of the decomposed atmosphere O2 is controlled to be less than 3% for 60 to 90 minutes.

7. The processing method according to claim 1, characterized in that: In step S4), the calcination time is 13 to 17 minutes.

8. The processing method according to claim 1, characterized in that: In step S5), the mass ratio of the phosphogypsum to the fly ash is 3-5:10-15.

9. The processing method according to claim 1, characterized in that: In step S5), the mass ratio of the cement clinker to the mixed material is 80-90:10:

20.

10. The processing method according to claim 1, characterized in that: In step S5), the specific surface area of ​​the ground cement product is controlled to be 300-350m 2 / kg.